Dynamics of Cocoa Bean Pulp Degradation during Cocoa Bean Fermentation: Effects of Yeast Starter Culture Addition - Laras Cempaka; Lienda Aliwarga; Susanto Purwo; Made Tri Ari Penia Kresnowati (Journal of Mathematical and Fundamental Sciences, 2014)
Fermentation is a crucial step in the post-harvest  processing of cocoa beans.  This  process  comprises  mixed  culture  microbial  activities  on  the  cocoa bean pulp,  producing  metabolites  that  act  as  important  precursors  for  cocoa flavour development. Variations in the microbial population dynamics during the  fermentation  process  may  induce  changes  in  the  overall  process.  Thus,  the introduction of a specific microbial starter culture may improve the quality of the fermentation. This article discusses the effects ofthe addition of  Saccharomyces cerevisae var.  Chevalieri  starter  culture  on  cocoa  bean  fermentation.  The dynamics  in  the  yeast  concentration,  sugary  pulp  compounds  and  metabolic products  were  measured  during  fermentation.  The  alterations  in  the dynamic metabolite  profile  were  significant,  although  only  a  slight  difference  was observed in the yeast population. A higher fermentation index was measured for the cocoa bean fermentation with yeast starter culture, 1.13 compared to 0.84. In conclusion,  this  method  can  potentially  be  applied  to  shorten  the  cocoa  bean fermentation time.